Huge fibroid uterus mimicking an ovarian malignancy - Guleria, Sara; Thakur, Suman; Pathania, Kushla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Leiomyoma of the uterus is the most common benign tumor arising from uterine smooth muscle. This is a case of a woman with an exophytic uterine leiomyoma mimicking an ovarian neoplasm. The potential for uterine leiomyomas to grow to an extreme size before causing symptoms is quite remarkable. This is likely due to the relatively large volume of the abdominal cavity, the distensibility of the abdominal wall and the slow growth rate of these tumors. In our case report, despite a fibroid of size reaching up to 34 weeks of gestation, our patient had minimal symptoms except for abdominal discomfort. There were no symptoms related to abnormal uterine bleeding or abnormal bowel or bladder habit. Also, the history and clinical examination of the patient favored a diagnosis of ovarian malignancy.